Action of adenosine receptor antagonists on hypoxia-induced effects in the rat hippocampus in vitro. - Croning, M. D. (1995)
1. We have studied three hypoxia-induced phenomena in the CA1 stratum pyramidale of the rat hippocampal slice: (a) the increase in extracellular potassium ion concentration ([K+]e) measured with ion-sensitive microelectrodes, (b) the intracellularly-recorded pyramidal cell hyperpolarization and (c) the extracellularly-recorded depression of the synaptically-evoked field potential recorded in stratum pyramidale. 2. The extracellular potassium ion concentration ([K+]e) rose from 3 mM to 4.1-4.4 mM at a time when the pyramidal cells hyperpolarized by about 6 mV and neurotransmission was virtually abolished. 3. Presumed glial cells depolarized in response to hypoxia. The shape and time course of this response was remarkably similar to the rise in [K+]e so induced. This is consistent with findings that glial cell membrane potential is dependent on transmembrane K+ gradient. 4. We investigated the effects of theophylline (100 microM) and 1,3-dipropyl-8-cyclopentylxanthine (DPCPX, 0.1 microM) on these effects. We have found that these compounds attenuated by about half the hypoxia-induced increase in [K+]e; however, they did not reduce the hypoxia-induced hyperpolarization. We have confirmed that they dramatically reduced the suppression of excitatory transmission caused by the hypoxia. We conclude that adenosine A1 receptors may be involved in the alteration of K+ homeostasis in the hippocampal slice during hypoxia.